Skorsing dan Sanksi Administratif bagi Prajurit TNI bagi Prajurit yang Melakukan Pelanggaran Hukum - Tetty Melina Lubis; Tiarsen Buaton; Arief Fahmi Lubis; Parluhutan Sagala (Pusat Riset dan Inovasi Nasional, 2022)
The provision of suspension sanctions and administrative sanctions is intended as an effort to train personnel and to provide a deterrent effect for law violators, as well as to prevent being imitated by other TNI soldiers. The purpose of this study is to show that TNI soldiers are different from civilians who are only bound by general legal rules, TNI soldiers in addition to being bound by general legal rules are also bound by military legal rules (military discipline law and military criminal law), so it can be said that it is not easy for a TNI soldier when faced with the enforcement of legal rules Qualitative research uses a descriptive approach to collect data systematically, factual, and fast according to the picture when the research is carried out. The results of this study show that for TNI soldiers who violate the law, being suspended and administrative sanctions are two things that are closely related to the legal process and personnel development, this condition causes a separate burden for a TNI soldier who violates the law because it has an impact on his career and income.